Snowy flowy blowy : a twelve months rhyme - Tafuri, Nancy (New York : Scholastic Press, 1999)
Rhyming text provides a descriptive word for each month of the year and takes a country family through the changes and surprises of the year's cycle.
"Based on an old poem by Gregory Gander."
Keywords: Months -- Fiction; Seasons -- Fiction; Stories in rhyme